2006
DOI: 10.1093/jac/dkl206
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and toxicological profile of the new biocide Akacid plus(R)

Abstract: These preliminary results demonstrate the broad antimicrobial properties of Akacid plus, which makes it a promising tool for topical application in the prophylaxis and treatment of bacterial and fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 9 publications
3
31
0
1
Order By: Relevance
“…Other previous studies have demonstrated that PHMGH, the active ingredient of the new AKWATON-based disinfectant, is an odourless, colourless and noncorrosive polymer with high solubility in water [22] and is significantly less toxic and harmless than currently used disinfectants [14,23] to humans and animals at a concentration ≤ 1%. In addition, cell cultures and the different tests carried out by Oulé et al [20], showed that the new AKWATON-based disinfectant killed fewer animal cells than the commercial disinfectants, sparing 80% of rat pancreatic (C2C12) cells and 65% of muscle RnM5F cells, whilst some of the well-known disinfectants currently on the market killed 85-100% of those cells.…”
Section: Introductionmentioning
confidence: 97%
“…Other previous studies have demonstrated that PHMGH, the active ingredient of the new AKWATON-based disinfectant, is an odourless, colourless and noncorrosive polymer with high solubility in water [22] and is significantly less toxic and harmless than currently used disinfectants [14,23] to humans and animals at a concentration ≤ 1%. In addition, cell cultures and the different tests carried out by Oulé et al [20], showed that the new AKWATON-based disinfectant killed fewer animal cells than the commercial disinfectants, sparing 80% of rat pancreatic (C2C12) cells and 65% of muscle RnM5F cells, whilst some of the well-known disinfectants currently on the market killed 85-100% of those cells.…”
Section: Introductionmentioning
confidence: 97%
“…Chlorhexidine (CHX) is an excellent cationic antiseptic that belongs to a class of drugs called biguanides and has the chemical name (1,1'-hexamethylenebis{5-(p-chlorophenyl)biguanide)} (Buxbaum et al, 2006;USP, 2008;BP, 2010;EP, 2011). It exists as a variety of salts, including acetate, gluconate, hydrochloride and digluconate, but the digluconate form (Figure 1) is the most soluble in water and at physiological pH (EP, 2011;Thomas et al, 2000;Martindale, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is most likely the most widely used biocide in antiseptic products, specifically in hand-washing and oral products; it is also used to impregnate catheters or other medical products, as a preservative in vaginal gel, as a disinfectant (Cone et al, 2006;Galice et al, 2006) and as a surgical scrub to clean the site of surgery (Buxbaum et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of cationic antimicrobial polymer, polyhexamethylene guanidine hydrochloride (PHMG) possesses great potential in the development of highly effective antimicrobials [8][9][10][11][12][13] and covalently binds permanent sterilesurface materials [14,15] for hospital infection control. We have recently reported that the cytoplasmic membrane disruption of bacteria cells induced by PHMG-membrane interactions is the main antibacterial mechanism by micrographic observations of Escherichia coli cells exposed to PHMG [9,16].…”
Section: Introductionmentioning
confidence: 99%